POTENSI SUMBER DAYA WILAYAH DALAM MENDUKUNG PERWUJUDAN KAWASAN AGROPOLITAN DI KABUPATEN MOROWALI - AS, Nur Syam (Teknosains, 2011)
This research aim to to analyse the potency of each subdistrict region  and marketing prospect in Regency Morowali which can be developed as area agropolitan. Analysis method used[by assessment of availability and requirement iprastucture of pursuant to SPM, then calculating  regional potency according to subdistrict by LQ analyse, and determination analyse of klasifikasi subdistrict clasificated according to its development by using determination method of DPP in KTP2D that came from Department Kimraswil. This research Result, 10 subdistrict region from 13 subdistrict can be developed as region agropolitan. While according to development of area agropolitan as much 3 area covering development of area of agropolitan Bungku, Kolonodale And Beteleme.Supporting  the agropolitan area in Regency Morowali still be limited and non meaning that the concept cannot be conducted. Key word: region, resources, developed,agropolitan